Risk Factors for Thromboembolism in the Population of Cancer and Hospice Patients - Michał Leśkiewicz; Piotr Daniel; Justyna Składanek; Karina Otręba; Joanna Cieszkowska; Karolina Czupryńska (Kazimierz Wielki University, 2024)
Venous thromboembolism (VTE) is a significant cause of death among palliatively treated patients. So far, numerous studies have been conducted on the general population. As a result, special scales were created to assess the risk of VTE or the probability of its occurrence. Among patients with terminal disease, there are much fewer publications discussing the problem of VTE. Hospice care patients constitute a special group due to their epidemiological structure and accompanying diagnoses. The most common are malignant tumors and heart failure. For this reason, they are particularly vulnerable to VTE events. This article reviews the literature on risk scales such as The Padua Risk Assessment Scale, Khoran score, Wells scale, PVFS scale and VTE-BLEED scale. W also present risk factors which contribute to the development of the VTE as well as to a more serious course of VTE. We discuss the epidemiological structure of patients, the impact of cancer as well as the chemotherapy used to treat it. We discuss the epidemiological structure of patients, the impact of cancer as well as the chemotherapy used in its treatment. We describe how the presence of a catheter and immobilization contribute to the development of VTE. We focus particularly on scales and risk factors to which a patient with a terminal disease is exposed. More research is needed in the future to better predict VTE in hospice patients. We hope that this work will increase awareness and encourage researchers to expand knowledge in this area.